2006
DOI: 10.1002/j.0022-0337.2006.70.12.tb04230.x
|View full text |Cite
|
Sign up to set email alerts
|

General Dentists’ Evaluation of Anesthesia Sedation Education in U.S. Dental Schools

Abstract: To assess the quality and quantity of sedation education in U.S. dental schools, a prospective, questionnaire-based survey was administered to general dental practitioners who graduated in 2003. Questionnaires were sent via facsimile to recent dental graduates using a list obtained through the American Dental Association. The response rate was 54 percent; 718 of the 1,328 nine-question surveys were returned. The response to the questionnaires indicates a perceived need for sedation care by the majority of rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…In Moore et al's survey of dental school graduates from 2003 to 2007, 44% of general dentists reported that a lack of training/experience or knowledge was a major reason for not offering sedation in their general dental practices, and the respondents’ written comments indicated a desire for a greater number of clinical experiences involving sedation procedures in the predoctoral curriculum 24 . In 2006, Boynes et al assessed the quality and quantity of sedation education in U.S. dental schools among general dental practitioners who had graduated in 2003 19 . Their responses also indicated a perceived need for sedation care by the majority of recent graduates and low overall satisfaction with the quality of sedation education in U.S. dental schools.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Moore et al's survey of dental school graduates from 2003 to 2007, 44% of general dentists reported that a lack of training/experience or knowledge was a major reason for not offering sedation in their general dental practices, and the respondents’ written comments indicated a desire for a greater number of clinical experiences involving sedation procedures in the predoctoral curriculum 24 . In 2006, Boynes et al assessed the quality and quantity of sedation education in U.S. dental schools among general dental practitioners who had graduated in 2003 19 . Their responses also indicated a perceived need for sedation care by the majority of recent graduates and low overall satisfaction with the quality of sedation education in U.S. dental schools.…”
Section: Discussionmentioning
confidence: 99%
“…While there has been research about IV‐sedation education in dental schools, 17 , 19 , 20 no study so far has inquired specifically how graduates from endodontic residency programs evaluate their education in this context. This might be partly due to the fact that the CODA standards for endodontic programs do not include a requirement that these graduates need to be competent to provide moderate IV‐sedation 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a 2005 national survey of general practitioners recently graduated from U.S. dental schools, 76.4% of the respondents perceived that their education in enteral sedation was below average or poor, and 67.9% perceived their education in intravenous sedation was below average or poor (1). 2 However, a national survey of the Canadian population disclosed a high level of desire among dental patients for sedation and anesthesia across all disciplines 3 …”
Section: Discussionmentioning
confidence: 99%
“…In summary, Spain shares a series of international factors that seriously affect the oral health of its population and require consensus‐based training in CS to enable recent graduates to use this technique safely, a task not exempt from difficulties according to the universities of different European and non‐European countries who share our concerns, including the United Kingdom and Ireland (Leitch & Jauhar, ), the United States (Boynes, Lemak, & Close, ), Australia (Moore, Boynes, Cuddy, Giovannitti, & Zovko, ), Japan (Morse, Sano, Fujii, & Kanri, ), and Jordan (Al‐Shayyab, Ryalat, Dar‐odeh, & Alsoleihat, ).…”
Section: Introductionmentioning
confidence: 99%